Curcumin and Novel Synthetic Analogs in Cell-Based Studies of Alzheimer’s Disease - Gagliardi, Stella; Franco, Valentina; Sorrentino, Stefano; Zucca, Susanna; Pandini, Cecilia; Rota, Paola; Bernuzzi, Stefano; Costa, Alfredo; Sinforiani, Elena; Pansarasa, Orietta; Cashman, John R.; Cereda, Cristina (Frontiers in Pharmacology, 2018)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder that is associated with the most common type of dementia and is characterized by the presence of deposits of the protein fragment beta-amyloid (Aβ) in the brain. The natural product mixture of curcuminoids that improves certain defects in innate immune cells of AD patients may selectively enhance Aβ phagocytosis by alteration of gene transcription. In this work, we evaluated the protective effects of curcuminoids in cells from AD patients by investigating the effect of a panel of curcuminoids on NF-kB and BACE1 signaling pathways by gene expression profiling on the clearance of Beta Amyloid (Aβ). Bisdemethoxycurcumin (BDC) showed the most potent protective action to reduce levels of NF-kB and BACE1, decrease the inflammatory cascade and diminish Aβ aggregates in cells from AD patients. Moreover, mannosyl-glycoprotein 4-beta-N-acetylglucosaminyltransferase (MGAT3) and vitamin D receptor (VDR) gene mRNAs were up-regulated in peripheral blood mononuclear cells from AD patients treated with BDC. BDC treatment impacts both gene expression, such as Mannosyl (Beta-1,4-)-Glycoprotein Beta-1,4-N-Acetylglucosaminyltransferase, Vitamin D and Toll like receptors and Aβ phagocytosis. Down-regulation of BACE1 and NF-kB following administration suggests a method to treat asymptomatic AD patients with selective curcumins as a dietary supplement.